PENGGUNAAN MEDSOS TIK TOK DENGAN KESEHATAN MENTAL EMOSIONAL DI SMK N KARANGANYAR - Cahyaningtyas, Anindhita Yudha; Akfiliantika, Devi Nanda Ayu (STETHOSCOPE, 2025)
Adolescents' emotional mental health is a health problem that needs attention. Considering the high levels of anxiety, stress and depression in teenagers, it can affect teenage productivity. As time goes by, technology is created to make human life easier, social media (social media) is widely used as a tool in communicating with other people, but it cannot be denied that its use can have an impact on the mental health of its users. The purpose of this research is to determine the relationship between the use of social media Tik Tok and mental health among teenagers at SMK N  Karanganyar. The design of this research is quantitative research using a cross sectional method. The number of samples in this research were students in class X and XI majoring in DKV at SMK N Karanganyar, totaling 138 respondents. Data from this research were analyzed using the chi square test. The results of this study show that there is a relationship between the use of social media Tik Tok and the emotional mental health of teenagers (p = 0.017), as evidenced by the calculated X² value (8.158) being greater than the X² table (5.591). It is hoped that the suggestions in this research can maintain emotional mental health by controlling and limiting oneself in using social media Tik Tok.